Clearance rates, arrest rates, and racial stratification: A time series analysis, 1965–2020 - Slepicka, Jessie (Journal of crime and justice, 2025)
Guided by the etiology of crime and policing literatures, this report presents the exploratory hypothesis that the overemphasis placed upon crime clearance rates as a measure of law enforcement efficiency/effectiveness may help account for longstanding racial disparities in the risk of arrest in the US. In the context of an increasingly quantitative fixation on measurable outputs within policing administration, it is argued that the oversurveillance, contact, and ultimate arrest of racial minorities, through discretionary proactive policing activities, has become embedded in the (sub)culture of policing to illustrate that something is being done about unsolved crime. In assessing this hypothesis, national-level, advanced time series models were estimated from 1965 to 2020 (N = 54), with results indicating that year-to-year increases in the lagged percentages of unsolved criminal offenses were significantly associated with year-to-year increases (decreases) in arrest rates for Black (White) people in the US – net of prior theoretically relevant macro-structural correlates of crime. The reported analyses represent a meaningful first attempt in assessing the validity of the hypothesized relationship between crime clearance percentages and trends in Black and White arrest rates – opening the door for a new line of inquiry within an already important field of stratification and crime.